PENGUATAN KEPRIBADIAN SISWA SMP BERBASIS AGAMA SEBAGAI ANTISIPASI DEGRADASI MORAL DI ERA DIGITAL - Firdaus, Ahmad; Ningrum, Siti Utami Dewi (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This study investigates the role of strengthening the personality of students at the junior high school (junior high school) level with a religious approach in facing the challenges of moral degradation arising from the development of globalization. Globalization has had a positive impact in terms of technological progress and the exchange of information, but it has also caused a shift in traditional values that can threaten individual morality, especially students at the junior high school level. In order for students to overcome this challenge, a comprehensive approach is needed that involves religious factors in strengthening their personality. Using a method with a descriptive-analytical approach this research utilizes relevant literature sources, such as journals, mass media news, and scientific books. The results of this study indicate that moral degradation is a serious challenge faced by the younger generation. For this reason, to strengthen the personality of religion-based students, various parties must be involved, starting from the family, school, and community.